2005
DOI: 10.1007/s10450-005-5985-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual Reflux PSA Process Applied to VOC Recovery as Liquid Condensate

Abstract: A new pressure swing adsorption process was proposed for treatment of low-VOC-concentration air streams. Feed gas is supplied to the high pressure column at some intermediate position to divide it into an enriching and a stripping sections. A part of air stream leaving the high pressure column is returned to the low pressure column as stripping reflux while air stream leaving the low pressure column is returned totally to the high pressure column as enriching reflux. With this dual reflux policy, VOC vapor can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…McIntyre et al have reported the enrichment of a dilute mixture of 0.75 mol % C 2 H 6 in nitrogen up to 68.4 mol % C 2 H 6 with a recovery of 99.6% using duplex PSA. Experimental studies by Wakasugi et al show that it is possible to recover ethanol as liquid from a dilute vapor-gas mixture of ethanol (1.2 vol %) and air using duplex PSA with recovery close to 100%. Distillation of a ternary liquid mixture into three products, each rich in one component, using two heat-integrated columns is well-known as Petlyuk distillation .…”
Section: Introductionmentioning
confidence: 99%
“…McIntyre et al have reported the enrichment of a dilute mixture of 0.75 mol % C 2 H 6 in nitrogen up to 68.4 mol % C 2 H 6 with a recovery of 99.6% using duplex PSA. Experimental studies by Wakasugi et al show that it is possible to recover ethanol as liquid from a dilute vapor-gas mixture of ethanol (1.2 vol %) and air using duplex PSA with recovery close to 100%. Distillation of a ternary liquid mixture into three products, each rich in one component, using two heat-integrated columns is well-known as Petlyuk distillation .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that a feed gas stream with 20 mol.% CO 2 was enriched to 90 mol.% in the heavy product stream and stripped to 2.5 mol.% in the lean gas stream. Since then, several research 11–20 have proven that DR‐PSA processes showed high separation performance for various applications, such as CO 2 capture, hydrocarbon upgrading, and air separation. Bhatt et al 21 performed a series of experiments for concentrating 5 mol.% CH 4 in N 2 using the DR‐PH‐A process and Norit RB1 activated carbon adsorbents.…”
Section: Introductionmentioning
confidence: 99%